The Feminist Quest: Reimagining the Relationship between Language, Gender, and Identity in The Knife of Never Letting Go (2008) by Patrick Ness - Alice Penfold (International Journal of Young Adult Literature, 2023)
This article examines the ways in which contemporary young adult (YA) fantasy novels can create subversive spaces to question gender norms and ideologies that shape discourses. Contemporary YA fantasy novels, I argue, can draw attention to how language and gender are socially constructed and offer new ways of perceiving and defining a sense of self that challenges Western society’s dominant patriarchal ideology. Young readers can see themselves but also imagine different possibilities of who they should or could be. Through close textual analysis of The Knife of Never Letting Go by Patrick Ness (2008), and drawing upon feminist poststructuralism, Bakhtinian theory, and YA fantasy scholarship, I consider the ways in which this contemporary YA fantasy novel presents the interconnectedness of language, gender, and identity and how the physical and metaphorical converge through the quest motif. I explore how social structures and dominant norms, including monolithic and governing meanings in gender and language, can be subverted and critiqued, giving young protagonists – and young readers – the opportunity to challenge gendered norms in the process of identity formation.